Kinetics of reserve and irreversible processes of polymeric nanocomposition on the basic of poli-ε-kaprolakton - Привалко, Е. Г.; Полякова, О. В.; Тарасенко, Ю. В. (Proceedings of National Aviation University (archive), 2013)
Receipt results have a practical value for creation perspective nanocomposition on the basis of poli-ε-kaprolakton with the beforehand set operating descriptions. Worked out optimal metods of receipt of polymeric nanocomposition on the basis of poli-ε-kaprolakton and montmorillonit